Targeting Treatments to Health Disparities. (3rd May 2021) - Hunter, Sharon K; Hoffman, M Camille; McCarthy, Lizbeth; D'Alessandro, Angelo; Wyrwa, Anna; Noonan, Kathleen; Christians, Uwe; Nakimuli-Mpungu, Etheldreda; Zeisel, Steven H; Law, Amanda J; Freedman, Robert
Abstract: These initial data suggest that with prenatal vitamins and choline supplements, we might decrease one risk factor associated with poorer health outcomes disproportionally affecting Black families, ie, preterm birth. Dissemination of this research fulfills the principle of Justice in the Belmont Report, to ensure that participants from different racial, ethnic and socioeconomic groups receive benefits from research directed to their specific problems.